Performance Evaluation and Benchmarking of Intelligent Systems - Madhavan, Raj.; Tunstel, Edward; Messina, Elena; SpringerLink (Online service) (Boston, MA : Springer US, 2009)
Performance Evaluation and Benchmarking of Intelligent Systems presents research dedicated to the subject of performance evaluation and benchmarking of intelligent systems by drawing from the experiences and insights of leading experts gained both through theoretical development and practical implementation of intelligent systems in a variety of diverse application domains. This contributed volume offers a detailed and coherent picture of state-of-the-art, recent developments, and further research areas in intelligent systems. The chapters cover a broad range of applications, such as assistive robotics, planetary surveying, urban search and rescue, and line tracking for automotive assembly. Subsystems or components described in this book include human-robot interaction, multi-robot coordination, communications, perception, and mapping. Chapters are also devoted to simulation support and open source software for cognitive platforms, providing examples of the type of enabling underlying technologies that can help intelligent systems to propagate and increase in capabilities. Performance Evaluation and Benchmarking of Intelligent Systems serves as a professional reference for researchers and practitioners in the field. This book is also applicable to advanced courses for graduate level students and robotics professionals in a wide range of engineering and related disciplines including computer science, automotive, healthcare, manufacturing, and service robotics.
Metrics for Multiagent Systems -- Evaluation Criteria for Human-Automation Performance Metrics -- Performance Evaluation Methods for Assistive Robotic Technology -- Issues in Applying Bio-Inspiration, Cognitive Critical Mass and Developmental-Inspired Principles to Advanced Intelligent Systems -- Evaluating Situation Awareness of Autonomous Systems -- From Simulation to Real Robots with Predictable Results: Methods and Examples -- Cognitive Systems Platforms using Open Source -- Assessing Coordination Demand in Cooperating Robots -- Measurements to Support Performance Evaluation of Wireless Communications in Tunnels for Urban Search and Rescue Robots -- Quantitative Assessment of Robot-Generated Maps -- Mobile Robotic Surveying Performance for Planetary Surface Site Characterization -- Performance Evaluation and Metrics for Perception in Intelligent Manufacturing -- Quantification of Line Tracking Solutions for Automotive Applications.
Keywords: Computer science; Computer system failures; Artificial intelligence; Applied mathematics; Engineering mathematics; Control engineering; Robotics; Mechatronics; Computer Science; System Performance and Evaluation; Control, Robotics, Mechatronics; Artificial Intelligence (incl. Robotics).; Appl.Mathematics/Computational Methods of Engineering; Electronic books